Do Venture Capitalists Influence the Decision to Manage Earnings in Initial Public Offerings? - Morsfield, Suzanne G.; Tan, Christine E. L. (The Accounting Review, 2006)
Prior studies suggest that venture capitalists (VCs) play a monitoring role. We predict and find that IPO-year abnormal accruals are lower in the presence of VCs for a sample of 2,630 IPO firms during 1983–2001. Our findings are robust to controls for the endogenous choice of VC financing. We consistently find that the VC effect holds even when controlling for IPO lock-up provisions, VC partial cashing out subsequent to the IPO, and alternative proxies for earnings management. In addition, our findings do not support the claims of critics that VCs inflated earnings during the Internet IPO bubble. Finally, we provide some evidence that the lower earnings management associated with VC monitoring partially explains the superior post-IPO returns of VC-backed firms.